Professional and social competences in agrarian specialists: Theoretical aspects - RIDEI, Nataliia; GUSAK, Kateryna (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
We assessed the current knowledge towards forming professional and social competences in agrarian specialists. We analyzed the process of preparing agrarian specialists in higher education of Ukraine. We reviewed definitions of „professional competence of agrarian specialist” and „social competence of agrarian specialist”.